The Embodiment of Faith to Social Responsibility by the Tastafi Community in Aceh - Muhammad Riza; Ibnu Qodir (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
The Tastafi study group, one of Acehnese majlis ta‘līm, holds significant importance in shaping religious knowledge and moral values in Aceh, a province widely recognized for its deep-rooted religious traditions. This study investigates the impact of the Tastafi study group on Aceh society's religious understanding and morality. This research used a qualitative approach involving in-depth interviews with 30 participants of the Tastafi study group from various social and educational backgrounds. The collected data were analyzed thematically and employed Fowler’s faith development theory and Carroll’s social responsibility theory. The findings demonstrate that the Tastafi study group profoundly impacts religious understanding and morality in Aceh society. The study group also played a pivotal role in fostering compassion, empathy, and social responsibility among its participants. Moreover, the study group contributed to unity, teamwork, and social cohesion within the Aceh community.